Exploring the potential of arabinoxylan as structuring agent in model systems for gluten-free yeast-leavened breads. (September 2020) - Espinosa-Ramírez, Johanan; Garzon, Raquel; Serna-Saldivar, Sergio O.; Rosell, Cristina M.
Abstract: Although the beneficial effect of arabinoxylan (AX) has been recognized for breadmaking, the available information about the effect of these compounds in gluten-free systems is scarce. In the present study, maize AX was tested in gluten-free breads using a yeast-leavened lean formulation based on rice flour and corn starch and two shaping models: pans and by dropping dough. The effect of the AX level (0%–5%) and hydration (70%–85%) were determined. Breads produced were analyzed in texture, morphology and crumb structure. The breads from the pan shaping model did not show significant differences in the crumb hardness. Moreover, the control breads presented better springiness, cohesiveness and resilience compared to AX breads. For the breads from the dropping dough model, those containing AX had lower hardness and chewiness and higher 2D area, height, cell density and surface area compared to control breads, especially at higher AX levels. Yet, AX caused a detrimental effect in springiness, cohesiveness and resilience. The hydration affected the hardness, 2D area, height, cell density and mean cell area in breads containing AX, finding better results in breads with 80% water absorption. This research demonstrated that even when AX are capable to improve the hardness and crumb structure of gluten-free breads, they could cause a detrimental effect in other textural characteristics. Graphical abstract: Image 1 Highlights: A gluten free bread model was defined for assessing arabinoxylan structuring action. Hydration level significantly affected arabinoxylans functionality in gluten free systems. Structuring action of arabinoxylans was confirmed through texture and microstructure analysis. Arabinoxylans modified dough and crumb inner structure helping expansion. Rice based gluten free breads could be obtained with arabinoxylans as improvers.